Towards the humanization of care for children in hospitals (Revista Estudios Psicológicos, 2022)
There is scientific evidence that the physical environment in which health care is provided has an impact on the health and well-being of patients. This evidence and the need to comply with standards in childhood care make us increasingly aware of the importance of organizational and physical factors in the hospital environment for the quality of life of pediatric patients. In this sense, this work focused on the review of some considerations on humanization in the hospital context, as well as some measures adapted to the characteristics of the hospitalized child.
Keywords: hospitalized children; hospital; humanization; quality of life; care